2023
DOI: 10.1029/2023jd039251
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Aerosols on Electrification and Lightning Polarity in an Idealized Supercell Thunderstorm via Model Emulation

Mengyu Sun,
Zhanqing Li,
Tao Wang
et al.

Abstract: Aerosol effects on the lightning intensity and polarity of a continental supercell storm were investigated using a three‐dimensional lightning scheme within the Weather Research and Forecasting model. We find that both intra‐cloud (IC) and cloud‐to‐ground (CG) flashes are enhanced by the increasing number of cloud condensation nuclei (CCN), especially the percentage of positive CG (+CG) strokes peaking at 42%. Electrical characteristics of the storm varied in different aerosol scenarios through microphysical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…There is no significant observational evidence indicating that high aerosol concentrations increase cloud electrification in pyroCb storms. According to the sensitivity analysis presented in previous studies [34,36,39], there is a noticeable non-linear relationship between the values of positive and negative charge densities and aerosol concentrations which can significantly affect the cloud charge structure. However, this paper does not aim to determine any qualitative link between aerosol concentrations and electrification.…”
Section: Influence Of Aerosol Concentrations On Pyrocb Electrificationmentioning
confidence: 98%
See 1 more Smart Citation
“…There is no significant observational evidence indicating that high aerosol concentrations increase cloud electrification in pyroCb storms. According to the sensitivity analysis presented in previous studies [34,36,39], there is a noticeable non-linear relationship between the values of positive and negative charge densities and aerosol concentrations which can significantly affect the cloud charge structure. However, this paper does not aim to determine any qualitative link between aerosol concentrations and electrification.…”
Section: Influence Of Aerosol Concentrations On Pyrocb Electrificationmentioning
confidence: 98%
“…This process lowers the efficiency of droplet collisions, which delays and inhibits the formation of raindrops. Studies in [34][35][36][37][38][39] have identified a positive correlation between lightning activity and aerosol concentrations. Additionally, those works demonstrate that high aerosol concentrations can significantly enhance the electrification process, according to the bulk microphysical model, or even weaken the electrification on further increase.…”
Section: Introductionmentioning
confidence: 99%
“…Different nucleation schemes in simulations affect the participation of aerosols in the electrification process. Sun et al (2024) studied the effects of aerosols on the electrification and lightning based on the WRF-ELEC model (Fierro et al 2013) coupled with a sophisticated explicit charging parameterization (Saunders and Peck 1998) and three-dimensional lightning scheme (MacGorman et al 2001, Mansell et al 2005. They suggested that both IC, CG flashes and fraction of +CG are all increased by adding CCN concentrations through modifying the microphysical processes.…”
Section: Numerical Simulations Of Aerosol Effectsmentioning
confidence: 99%
“…Observations and numerical simulations suggest that adding aerosols to a pristine environment intensifies deep convection through aerosol-induced changes in the mixed phase layer of the cloud that enhance lightning (Fan et al, 2018;Sun et al, 2023Sun et al, , 2024. As the aerosol amount continues to increase, a larger population of tiny droplets begins to suppress the growth of graupel and the delivery of large, supercooled droplets to the mixed phase region thus suppressing charge separation and flash rates (Williams et al, 2002).…”
mentioning
confidence: 99%